Practitioners’ Views on Computerized Drug–Drug Interaction Alerts in the VA System - Ko, Yu (American Medical Informatics Association, 2007)
OBJECTIVES: To assess Veterans Affairs (VA) prescribers’ and pharmacists’ opinions about computer-generated drug–drug interaction (DDI) alerts and obtain suggestions for improving DDI alerts. DESIGN: A mail survey of 725 prescribers and 142 pharmacists from seven VA medical centers across the United States. MEASUREMENTS: A questionnaire asked respondents about their sources of drug and DDI information, satisfaction with the combined inpatient and outpatient computerized prescriber order entry (CPOE) system, attitude toward DDI alerts, and suggestions for improving DDI alerts. RESULTS: The overall response rate was 40% (prescribers: 36%; pharmacists: 59%). Both prescribers and pharmacists indicated that the CPOE system had a neutral to positive impact on their jobs. DDI alerts were not viewed as a waste of time and the majority (61%) of prescribers felt that DDI alerts had increased their potential to prescribe safely. However, only 30% of prescribers felt DDI alerts provided them with what they needed most of the time. Both prescribers and pharmacists agreed that DDI alerts should be accompanied by management alternatives (73% and 82%, respectively) and more detailed information (65% and 89%, respectively). When asked about suggestions for improving DDI alerts, prescribers most preferred including management options whereas pharmacists most preferred making it more difficult to override lethal interactions. Prescribers and pharmacists reported primarily relying on electronic references for general drug information (62% and 55%, respectively) and DDI information (51% and 79%, respectively). CONCLUSION: Respondents reported neutral to positive views regarding the effect of CPOE on their jobs. Their opinions suggest DDI alerts are useful but still require additional work to increase their clinical utility.